Teacher-Student Interaction and Secondary School Student Academic Performance in Ekiti State, Nigeria - Dapo Alonge, Bolarinwa; Grace Funmilayo, Olusegun; Omowumi Victoria, Ayodele (International Research in Education, 2022)
The study investigated the relationship between teacher-student interaction and secondary school student academic performance in public secondary schools in Ekiti State, Nigeria. Descriptive survey and correlational research methods were employed for the study. The Teacher-student Interaction Questionnaire (TSIQ) was used to collect data from a sample of 1,074 respondents. A validated inventory was also used for the study. Proportionate simple random sampling technique was used to select 376 teachers and 707 students from 24 public secondary schools in the state. The study revealed that there was a significant positive relationship between teacher-student interaction and secondary school student academic performance in public secondary schools in Ekiti State, Nigeria. It was concluded that teacher-student interaction has a positive influence on secondary school student academic performance in Ekiti State, Nigeria. It has been established that teachers-students interaction is one of the determinants of secondary school student academic performance.